Healthcare workers and adult patients preferences of hospital built environment. Survey in ordinary surgery and medical oncology ward at the Italian National Oncology Institute - Brambilla, Andrea; Perotti, Gabriele Mario; Villa, Valentina; Nuvolari-Duodo, Isabella; Triarico, Antonio; Nicora, Carlo; Capolongo, Stefano (Frontiers in Health Services, 2025)
BackgroundExperience is an important factor in hospitalisation and treatment processes, especially in oncology. The preferences of patients and health workers have recently been increasingly considered as key elements for supporting clinical and organisational performances. The relationship between staff and patients preferences and the quality of hospital built environment is also an important aspect but it is still underexplored in the scientific literature.AimThe study aims to understand both qualitatively and quantitatively how the hospital built environment influences the well-being of patients and staff in ordinary surgery and medical oncology ward of a national institute for oncology in Northen Italy.MethodsThe research was carried out according to the following methodological sequence: (i) identification of the target and setting; (ii) elaboration of a questionnaire with 22 items; (iii) administration of the questionnaire on a sample of patients and health professionals; (iv) data collection in a dedicated database; (v) data analysis and interpretation.ResultsA total of 521 adult oncology patients and 311 health workers participated in the study. The findings highlight differences and similarities of preferences among patients and staff regarding built environment features that are reported in scientific literature. For example, patients shows limited interest in the possibility of having a single room (only 31% report it as very important), while from the staff point of view, there is a predominantly importance-oriented distribution with 51% and 83% of the respondents that consider this to be of great relevance respectively for their practice and for the patient experience.ConclusionThe findings underline the importance of considering the perspectives of oncological patients and healthcare workers in the assessment of oncology wards for future evidence-based hospital design.